(untitled) (CIPEEX, 2024)
THE PROJECT IS A SOFTWARE FOR SCHEDULING AND MANAGING MEDICAL APPOINTMENTS OVER THEINTERNET. IT AIMS TO SIMPLIFY THE BOOKING OF APPOINTMENTS IN THE PRIVATE NETWORK, WITH PLANS TOEXPAND TO THE PUBLIC NETWORK. THE SOFTWARE IS ACCESSED BY DOCTORS, SECRETARIES, AND PATIENTS,ALLOWING THEM TO SCHEDULE APPOINTMENTS AND MANAGE MEDICAL SCHEDULES. THE MAIN OBJECTIVEIS TO FACILITATE THE SCHEDULING OF MEDICAL APPOINTMENTS AND OPTIMIZE THE AVAILABLE SCHEDULES.THE SOFTWARE WILL ALSO PROVIDE REPORTS TO ASSIST IN APPOINTMENT OPTIMIZATION. IT USESJAVASCRIPT/TYPESCRIPT WITH REACT FOR THE WEB VERSION AND REACT NATIVE FOR MOBILE, ALONG WITHA BACKEND IN NEST.JS. THE PLATFORM OFFERS A REAL-TIME SHARED SCHEDULE AND BUSINESS RULESFOR APPOINTMENT CONTROL.THE SOFTWARE PROVIDES THE ABILITY TO VIEW THE SCHEDULES OF VARIOUS DOCTORS AND THEIR AVAILABLETIME SLOTS, ALLOWING PATIENTS TO SCHEDULE APPOINTMENTS QUICKLY AND CONVENIENTLY. THISELIMINATES THE NEED TO CALL MEDICAL OFFICES TO MAKE APPOINTMENTS. THE PROJECT USES AGILEMETHODOLOGIES, SUCH AS SCRUM, AND A VISUAL TASK MANAGEMENT SYSTEM, SUCH AS TRELLO, TOORGANIZE DEVELOPMENT.THE CREATION OF A PROCESS FLOW AND THE DEFINITION OF INITIAL TASKS ESTABLISH A SOLID FOUNDATIONFOR FUTURE DEVELOPMENT. THE PROJECT HAS THE POTENTIAL TO POSITIVELY IMPACT THE HEALTHCARESECTOR, MAKING THE MANAGEMENT OF MEDICAL APPOINTMENTS MORE EFFICIENT AND ACCESSIBLE. THENEXT STEPS WILL INVOLVE CREATING PROTOTYPES, CODING, AND IMPLEMENTING THE MENTIONEDTECHNOLOGIES